FORMULASI PASTA GIGI EKSTRAK ETANOL BUAH PALA (Myristica fragrans Houtt.) - Gratia, Berta; Yamlean, Paulina V.Y.; Mansauda, Karlah L.R. (PHARMACON, 2021)
ABSTRACTNutmeg (Myristica fragrans Houtt.) is a plant with the main compounds of essential oils, terpenoids and aromatic compounds. This study aimed to determined the optimum composition of Na CMC in the toothpaste preparation of nutmeg ethanol extract. It used the trial and error method to determined some variations composition of Na CMC (2%; 4%; 6%; 8%). A formulation of toothpaste was performed by levigation method. Determination of the composition was based on the result of the physical examination of the best and qualified preparations, included organoleptic test, homogeneity test, spreadability test, adhesion test, syneresis test and pH test. The results showed that the composition of Na CMC was 4%. Keywords: Nutmeg, Toothpaste, Na CMC. ABSTRAKPala (Myristica fragrans Houtt.) merupakan tumbuhan yang memiliki senyawa utama minyak atsiri, terpenoid dan senyawa aromatik. Penelitian ini bertujuan untuk menentukan konsentrasi optimum Na CMC pada sediaan pasta gigi ekstrak etanol buah pala. Metode yang digunakan untuk menentukan konsentrasi Na CMC (2%; 4%; 6%; 8%) ialah trial and error. Pembuatan pasta gigi dilakukan menggunakan metode levigasi. Penentuan komposisi didasarkan pada hasil uji pemeriksaan fisik sediaan yang terbaik dan memenuhi syarat, diantaranya uji organoleptik, uji homogenitas, uji daya sebar, uji daya lekat, uji sineresis dan uji pH. Hasil penelitian menunjukkan komposisi Na CMC ialah 4%. Kata kunci: Pala, Pasta gigi, Na CMC.